Performance enhancement of DFBL based near‐infrared CH4 telemetry system using a focus tunable lens. Issue 4 (21st November 2020) - Li, Guolin; Ma, Kun; Jiao, Yue; Jiang, Qingzhi; Zhang, Xuena; Zhang, Zecheng; Wu, Yunhui; Song, Di
Abstract: A methane telemetry system for 1653 nm DFB laser based on TDLAS‐WMS technology is developed in this article. The focus tunable lens is used as the collimating system of the telemetry device to solve the problem that the telemetry device cannot be dynamically adjusted under different detection environments. Experimental results show that the root mean square error was 7.6205 and the theoretical limit of detection (LoD) was 1.473 parts per million (ppm) while the optimal integration time reaches 30 s. The near‐infrared CH4 telemetry system is suitable for different detection environments of natural gas leakage and has good detection performance and stable and reliable operation.